INITIAL PERCEPTION OF A PATIENT WITH HORNER SYNDROME: A CASE STUDY - Gerónimo Flores, Nayeli Cristhell; Álvarez de Dios, Jesús Antonio; Magaña Mendez, Argentina; Mendoza Jiménez, Karina Michelle (Kuxulkab', 2022)
Horner syndrome is a disease that encompasses a condition that occurs in a specific area of the body. Therefore, the objective of the present work is to show the main symptoms of onset and the damage it causes to the subject suffering from the disease, providing information from a case study. For this, the case of a patient who suffered from Horner's syndrome was reviewed. It was observed that the syndrome is detected by the presence of phenotypic pathologies in the patient, for example, palpebral ptosis. Similarly, what was the follow-up of the patient was covered, within this it is reported that the treatment applied, considering the conditions, was positive after one month of treatment. The patient made a full recovery.
Keywords: Disease; Phenotype; Symptoms